BENTUK DAN FUNGSI KESENIAN TRADISIONAL TONG-TONG PREK DESA JATIREJO KECAMATAN AMPELGADING KABUPATEN PEMALANG (Jurnal Seni Musik, 2014)
Traditional Art â€œTong-Tong Prekâ€ of Desa Jatirejo Kecamatan Ampelgading Kabupaten Pemalang is the only one traditional art of tong-tong prek in Desa Jatirejo. Traditional Art â€œTong-Tong Prekâ€ of Desa Jatirejo Kecamatan Ampelgading Kabupaten Pemalang can produce a unique music. The purpose of the music of â€œtong-tong prekâ€ actually to wake the people up in fasting month, but in that village the music of â€œtong-tong prekâ€ not only becomes a music to wake the people up, but also to be a show for the people. In the other town, it is also called â€œThek-Thekâ€ or â€œThong-Thong Lekâ€. The musics that produced in this traditional art are campursari tone with song lyrics that they produce by themselves. The themes of the songs are about islamic, peopleâ€™s lives, and also about neightborhood security system (siskamling). The objective of this research is to find the type and the function of Traditional Art â€œTong-Tong Prekâ€ of Desa Jatirejo Kecamatan Ampelgading Kabupaten Pemalang.